POSSIBILITIES OF EFFECTIVE USE OF HUMAN RESOURCES IN THE NATIONAL LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The human capital of the world's countries and the level of its use are linked using various international indices. In these indices, the leading positions are occupied by countries with high scientific and technical potential, scientific and modern research, investment in capital and stability, efficiency indicators, and cost. This is one of the main indicators for assessing the effectiveness of the use of human resources.In world practice, the effective use of available human resources is considered the most relevant and its importance is increasing every day. Improving the system for assessing the effectiveness of the use of human resources in the country is determined by increasing their competitiveness.
Keywords: labor market, human resources, human capital, Russia, globalization, labor relations, underemployment, employment status, inactive population, active population.